The Philippines’ response to the Covid-19 pandemic learning from experience and emerging stronger to future shocks (Philippine Institute for Development Studies (PIDS), 2022)
The coronavirus disease 2019 (COVID-19) pandemic hit the Philippine economy and society unprecedentedly. To protect the people, the government had to act decisively and identify solutions to contain the rapid spread of the virus and the devastating economic and social disruption caused by the pandemic. This book compiles papers assessing the strategies, policies, and recovery efforts that the government had implemented during the first year of the COVID-19 pandemic. It discusses the challenges that the country had experienced and the government's responses in the areas of health, macroeconomy, food security, labor, social protection, poverty, education, digitalization, fiscal policy, and crisis and risk communication. Learning from these experiences, this book provides recommendations to help the Philippines recover from the current crisis and build better resilience to future shocks.